Health complaints and use of medicines among adolescents in Malta - Darmanin Ellul R; Cordina M; Buhagiar A; Fenech A; Mifsud J (Pharmacy Practice, 2008)
Objective: To investigate self-reported health complaints and the use of medicines among adolescents in Malta.Methods: A self-administered questionnaire was used to survey self-reported health complaints, the use and the sources of medicines that had been accessed, during the preceding 3 months among adolescents attending secondary schools in Malta. A stratified random sample design generated a sample size of 514 students. The health complaints and use of medicines that were investigated included ear problems/hay fever/cold/cough, headache, skin problems, sport injuries, indigestion/diarrhoea/constipation, eye problems and menstrual pain (for girls). The use of vitamins and antibiotics was also investigated. Results: A total of 477 students participated in the final data collection. Correct information was submitted by 474 students, (aged 14-16 years), who formed the analytical sample, of which 53.8% were girls. The students reported a mean number of 2.70 (SD = 1.39) out of a total of 7 health complaints and 90.3% reported using at least 1 medicine during the preceding 3 months. The community pharmacy was cited as the most commonly accessed source for most of the medicines that were investigated. A proportion of 24.3% of the students had taken at least 1 medicine without adult guidance during the preceding 3 months. Almost 10% of those who had taken antibiotics, had accessed them from the home medicine cabinet.Conclusion: A high proportion of adolescents in Malta reported the use of medicines to alleviate the symptoms of common health complaints. This result is concordant with previous research carried out in the United Kingdom, Germany, Slovakia and Kuwait. A considerable proportion of students in this study had obtained medicines without adult guidance and accessed antibiotics from the home medicine cabinet. This highlights the importance of carefully designed education programs for adolescents that will integrate information about the proper use of medicines.